2011
DOI: 10.1097/aog.0b013e3182118d59
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Women With Physical Disabilities

Abstract: The Eunice Kennedy Shriver National Institute of Child Health and Human Development sponsored a 2-day workshop to assess the body of evidence on pregnancy in women with physical disabilities, identify gaps in knowledge, and formulate recommendations for further research. A multidisciplinary group of experts discussed available data on pregnancy outcomes among women with varying physically disabling conditions, medical and psychosocial risks for mothers and children, and barriers to prenatal care and parenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
107
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 53 publications
4
107
0
4
Order By: Relevance
“…There are few studies that have shown that most disabled women will have good pregnancy outcomes; however, some data indicates that complications may be more prevalent among women with physical disabilities, according to the nature and severity of the underlying condition. Some researchers have shown that pregnant women with physical disabilities had higher rates of preterm deliveries, low birth weight infants, and pregnancy complications [18]. In those studies, visual impairment was not investigated as a chronic physical disability, but according to the Israel Ministry of Social Affairs it is considered a physical disability that needs special day-by-day instruments for orientation, mobility, reading, and adjusted access to facilities within the community.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies that have shown that most disabled women will have good pregnancy outcomes; however, some data indicates that complications may be more prevalent among women with physical disabilities, according to the nature and severity of the underlying condition. Some researchers have shown that pregnant women with physical disabilities had higher rates of preterm deliveries, low birth weight infants, and pregnancy complications [18]. In those studies, visual impairment was not investigated as a chronic physical disability, but according to the Israel Ministry of Social Affairs it is considered a physical disability that needs special day-by-day instruments for orientation, mobility, reading, and adjusted access to facilities within the community.…”
Section: Discussionmentioning
confidence: 99%
“…Le meilleur moyen de vider la vessie tout en minimisant le risque infectieux est de pratiquer des autosondages à raison d'au moins cinq fois par 24 heures (faire en sorte que le volume ne dépasse pas 400 mL d'urines par sondage). Il est par ailleurs conseillé d'augmenter les apports hydriques de manière à obtenir une diurèse quotidienne d'au moins 1,5 L [6,7].…”
Section: Discussionunclassified
“…Il apparaît par ailleurs nécessaire d'insister sur la prévention du risque thromboembolique (port de bas de contention, kinésithérapie, héparinothérapie en cas d'alitement) [7]. Une patiente de notre série, sans traitement prophylactique, a présenté une thrombose veineuse profonde proximale.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…32 It is thought to be a result of uncertain in utero events or brain damage from injury or infection in childhood. 33 Currently there are 400,000 adults living with CP in the United States, with 10,000 new cases occurring per year.…”
Section: Cerebral Palsymentioning
confidence: 99%